Pilot Study on the Impact of Evidence-Based Data on Oncology Pharmacists' Perceptions. (August 2014) - Renet, Sophie; Lebel, Denis; Prot-Labarthe, Sonia; Therrien, Roxane; Bourdon, Olivier; Bussières, Jean-François
Objectives: The main objective was to evaluate whether the level of agreement of oncology hospital pharmacists with statements on their impact is influenced by the presence or absence of evidence-based data. The secondary objective was to evaluate the relative importance of evidence-based data among factors that may have contributed to oncology pharmacy practice evolution. Methods: Oncology pharmacists' answered a Web questionnaire to measure their level of agreement with statements regarding their impact. Respondents answered the questionnaire before (pre) and after (post) being informed whether supporting evidence was available for each statement. Respondents were also asked to rank all of the factors in order of their perceived contribution to oncology pharmacy practice evolution. Results: A total of 64 questionnaires were obtained. Respondents reported a high level of agreement with statements regarding their impact on oncology pharmacy practice (mean agreement of 95.9% pre vs 93.8% post). A statistically significant diminution in the level of agreement was observed for 3 statements after respondents were informed that no supporting evidence was available for these statements. Respondents assigned a high importance to factors related to the perception of positive outcomes of pharmaceutical activities on patient safety, health care costs, and clinical results but a low importance to the use of evidence-based data.